Dubbing Star Wars: a journey to bridge the uncanny valley - Esteban, Anthony (2021)
This doctoral thesis examines the phenomenon of the uncanny valley, its relationship to genres of Imaginary Fiction (such as science-fiction, high fantasy…), the specificities of language in those genres, and ultimately its impact on the dubbing of films belonging to this genres. The corpus that is used to conduct this examination is the Star Wars series. The first part of this thesis explores the notion of the uncanny from a historical, as well as from a cognitive science perspective, with the goal of identifying the mechanics of the phenomenon and its impact on individuals. The second chapter is dedicated to a class of narrative storytelling that I call Imaginary Fiction, a set of genres that allows for the presence of non-human speaking characters. The section explores the idiosyncrasies of Imaginary Fiction, with a focus of the balance it creates between Cognitive Estrangement and Suspension of Disbelief, and their relation to the uncanny. In the Third chapter, I explore the particular utilisation of language in genres of Imaginary Fiction, both from a storytelling perspective, and from a linguistic perspective. This chapter is interested in the ways Imaginary Fiction uses alternative vocabulary as well as constructed languages to create Estrangement and Suspension of Disbelief. The fourth chapter of this thesis focuses on the practice of dubbing and on the uncanny sensation that it can evoke in viewers. The chapter breaks down the individual elements of dubbing in an effort to uncover the ways different stimuli can potentially conflict with another, therefore creating breakdowns in immersion. This chapter also argues that dubbing creates a shift in characterisation for protagonists, that impacts viewer experience. The fifth and final chapter comprises of two main case studies from the Star Wars series, that involve non-human characters. The aim of these studies is to further the relationship between lip synchronisation and the uncanny effect in dubbing, and to determine if the heightened levels of Estrangement and Suspension of Disbelief associated with genres of Imaginary Fiction in any way mitigates those effects This thesis concludes by a summary of its findings and suggestions for further research. It also explores technological ways media localisation might evolve in the future in an effort to offer a greater level of immersion and enjoyment to audiences all around the world.